سبل تحقيق التنمية المستدامة في العالم الإسلامي: الوقف الأخضر نموذجا - النويران، ثامر علي (جامعة عمار ثليجي الأغواط - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2017)
أصبحت التنمية المستدامة أحد أهم المؤشرات العالمية لاستمرارية البشرية في الوقت الحالي، كما أصبحت أبعاد التنمية المستدامة المختلفة إحدى أهم أولويات الدول من أجل الإصلاح والتحديث، ومن هذا المنطلق تشكل هدف هذه الدراسة في الوقوف على إحدى أساليب تحقيق التنمية المستدامة في العالم الإسلامي والمتمثلة بالوقف الأخضر، حيث تحاول هذه الدراسة إبراز دور الوقف الأخضر في تحقيق التنمية المستدامة في العالم الإسلامي، وذلك من خلال إبراز أهمية الوقف الأخضر التنموية، والتطرق لأهم آليات الوقف الأخضر في تحقيق التنمية المستدامة.
Sustainable development has become one of the most important global indicators of human continuity at the moment, as the various dimensions of sustainable development has become one of the most important priorities of the states for the reform and modernization, and this sense constitute objective of this study to stand on one of the methods of achieving sustainable development in the Islamic world and of the green halt, this study is trying to highlight the role of the green endowment in achieving sustainable development in the Islamic world, and this by highlighting the importance of green development moratorium, and addressed to the most important mechanisms of green endowment in achieving sustainable development.
Keywords: التنمية الاقتصادية -- أنواع الوقف -- العالم الإسلامي -- الرعاية الاجتماعية